The Analysis of Students' Learning Difficulties in Solving HOTS (Higher Order Thinking Skills) Mathematics Problems at SD Negeri 20 Banyuasin III - Hidayah, Noor; Aquami; Miftahul Husni; Al Ihwanah; Ines Tasya Jadidah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines the learning difficulties experienced by fifth-grade students in solving mathematics problems based on Higher Order Thinking Skills (HOTS) at SD Negeri 20 Banyuasin III. The aim of the study is to analyze the types and factors of difficulties as well as the strategies to overcome them. The research uses a descriptive phenomenological qualitative approach, involving 16 students and supporting informants selected through purposive sampling. Data were collected through structured observation guides, in-depth interview protocols, and documentation, and then analyzed interactively through data reduction, presentation, and conclusion drawing, along with triangulation validation. The findings indicate that students face significant challenges in understanding concepts, planning solutions, implementing strategies, and evaluating answers, influenced by low motivation, intellectual limitations, lack of parental support, and media distractions. The study concludes that teacher interventions such as motivation enhancement, problem-solving practice, and collaboration with parents help but are not yet fully effective. Further research is recommended to expand the sample and explore innovative interventions.